1968
DOI: 10.1103/physrev.175.1216
|View full text |Cite
|
Sign up to set email alerts
|

Paramagnetic NH3Cl and NH3Br Color Centers in Irradiated Ammoni

Abstract: Radiation-induced NH 3 C1 and NH 3 Br defect centers have been studied in ammonium halide single crystals by EPR and optical spectroscopy. The defects are most likely formed by removal of H° from an ammonium ion with subsequent bonding of NH 3 + to X~ along a (111) direction. In the NH3CI center, NH3 4 " is a nearly planar group loosely bonded to a Cl~~; in the NH 3 Br center there is more tendency toward sp z hybridization of the N orbitals, and stronger covalency within the nitrogen-halogen bond. The molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1970
1970
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Radiolysis of ammonium halide salts and alkylammoium halide salts has been shown to result in the production of halide containing radicals. 41,42 Some of these degradation products could likely react with Pb 0 , reforming the Pb 2+ , and even remain bound to the film resulting in a more amorphous PbI 2 . This could also help passivate defects and slowing the degradation of PbI 2 to Pb 0 .…”
Section: Resultsmentioning
confidence: 99%
“…Radiolysis of ammonium halide salts and alkylammoium halide salts has been shown to result in the production of halide containing radicals. 41,42 Some of these degradation products could likely react with Pb 0 , reforming the Pb 2+ , and even remain bound to the film resulting in a more amorphous PbI 2 . This could also help passivate defects and slowing the degradation of PbI 2 to Pb 0 .…”
Section: Resultsmentioning
confidence: 99%
“…NH,C1 is another centre [5] produced in NH,C1 crystals on X-irradiation at 77 K. It has an optical absorption band a t 375 nm which lies in the same region as the UV band of the V,-centre. Its ESR peaks also overlap with those of the V,-centre.…”
Section: Earlier Workmentioning
confidence: 99%
“…Its ESR peaks also overlap with those of the V,-centre. Hence NH,Cl was studied [5] by warming the crystal, X-irradiated at 77 K, little above 155 K and then cooling it back to 77 K. The ESR study of NH,CI has indicated an axially symmetric hyperfine pattern with the symmetry axis along a (111)-direction. This is stable up to 220 K only.…”
Section: Earlier Workmentioning
confidence: 99%
“…This effect may be seen directly in the electron paramagnetic resonance spectra of ND 3 Cl color centers [2] in deuterated single crystals. If these crystals are exposed to the atmosphere for short periods of time, proton hyperfi ne interactions from hydrogen which has exchanged with deuterium atoms in the ammonium group become pronounced in the spectra.…”
Section: Introductionmentioning
confidence: 99%
“…It was noted, during studies on radiation-induced point defects in ammonium halide single crystals [1,2], that hydrogen migrates fairly rapidly through these crystals at room temperature. This effect may be seen directly in the electron paramagnetic resonance spectra of ND 3 Cl color centers [2] in deuterated single crystals.…”
Section: Introductionmentioning
confidence: 99%